Research progress of standardization management of nosocomial infection control in the operating room (手术室医院感染规范管理研究进展) - XU Xu (徐旭); REN Guqun (任顾群); SU Yuqiang (苏玉强); WANG Yuena (王岳娜); XU Yuanle (许远乐) (中西医结合护理)
The operating room is an important place for patients to receive surgical treatment. The occurrence nosocomial infection may cause a serious impact on the surgical treatment and health status of patients, and even threaten the lives of patients. Therefore, good management of the operating room is of great significance for the treatment effect and health of patients. This paper summarized the relevant factors and standardized management measures of nosocomial infection in the operating room, hoping to provide reference for improvement of the management quality of operating rooms at all levels of medical institutions in China. (手术室作为患者接受手术治疗的重要技术场所, 一旦出现医院感染, 会对患者造成严重的负面影响, 因此做好手术室管理工作具有重要的意义。本研究通过对相关期刊资料的查询分析, 针对性总结了手术室医院感染相关因素和相应规范管理方法, 以期为各级医疗机构手术室管理质量的保障与提升提供参考。)